Field consideration of a waveguide applicator for superficial microwave hyperthemia - Omar, Rosli (1995)
In conjunction with other conventional forms of cancer theraphy, microwave hyperthermia appears to have synergistics effect and to be effective for certain types of antineoplastics treatments. One of the main challenges in hyperthermia research is the development of effective, non invasive applicators. This project investigates the feasibility of using a single Dielectically Open-ended Rectangular Waveguide Direct-contact Antenna (DORWDA) for depositing microwave energy into the human body for the treatment of superficial tumours. A distilled water-loaded DORWDA single applicator with a small aperture size (3.5 x 1.75 cm) has been developed for local hyperthermia application. The operation frequency is 915 MHz. The water loading provides a good coupling of the radiated power into tissue. Kirchhoff-Huygens principles and scalar theory of diffraction has been implemented. Using the above approach, a one-dimensional model has been developed for computing the field distribution from the aperture of the applicator as a function of depth in the human muscle.